2005
DOI: 10.1016/j.jcrs.2004.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine versus dapiprazole: Influence on pupil size at various illumination levels

Abstract: Pupil mydriasis at scotopic illumination levels was reduced by both drugs in a similar fashion. Because of the slightly stronger effect of brimonidine, application of this agent 20 minutes before activities in dimly lit areas or at night may be recommended for photic phenomena following refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…However, the effect of dapiprazole 0.25% was not as long lasting as that of brimonidine tartrate 0.20%, with many eyes in the dapiprazole group having a pupil width similar to that at baseline after 4 hours. This is similar to the findings of Marx-Gross et al, 22 who compared the effects of brimonidine and dapiprazole on pupil size under various illumination levels, and to those of Kesler et al, 23 who found significant miosis after instillation of brimonidine tartrate 0.2% ophthalmic solution.…”
Section: Discussionsupporting
confidence: 90%
“…However, the effect of dapiprazole 0.25% was not as long lasting as that of brimonidine tartrate 0.20%, with many eyes in the dapiprazole group having a pupil width similar to that at baseline after 4 hours. This is similar to the findings of Marx-Gross et al, 22 who compared the effects of brimonidine and dapiprazole on pupil size under various illumination levels, and to those of Kesler et al, 23 who found significant miosis after instillation of brimonidine tartrate 0.2% ophthalmic solution.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with previous reports of brimonidine's effect on pupil diameter in concentrations of 0.15% and 0.20%. [7][8][9][10][11] Brimonidine has been suggested as an optional treatment to reduce night-vision disturbances after refractive surgery, which occur mainly in patients with large pupils, small optical treatment zones, and higher-order aberrations. 9,10 Brimonidine 0.10% seems to have the same antimydriatic effect as its higher concentrated solutions.…”
Section: Discussionmentioning
confidence: 99%
“…McDonald et al 6 showed that it causes a significant decrease in pupil diameter only in the dark. Subsequent studies have established that the reduction in pupil diameter induced by brimonidine 0.2% is significant under dark luminance conditions 7,8 and have suggested its use in reducing night-vision disturbances, such as glare and halos, after refractive surgery. 9 The same effect has been demonstrated with the use of brimonidine 0.15%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements were done 1 h after dosing. Marx-Gross et al [4] report that the maximum miotic effect of brimonidine was seen after 40 min and remained stable 180 min after dosing. Consequently, we tested the effects of the eyedrops 1 h after administration of the medication.…”
Section: Methodsmentioning
confidence: 99%